Pengaruh Perencanaan Anggaran dan Pelaksanaan Anggaran Terhadap Serapan Anggaran Satuan Kerja Perangkat Daerah (SKPD) Pada Pemerintaha Kota Banda Aceh - Arfah Salwah (Jurnal Transformasi Administrasi, 2019)
This study aims to look at factors in the influence on the absorption of the SKPD budget within the Banda Aceh City Government. Two factors are believed to influence the absorption of the SKPD budget, namely: budget planning and budget implementation. There total 78 were choosen as respondents to this study. The report on the realization of the budget of the Banda Aceh City Government from 2014 to 2018 shows that the budget absorption of Regional Work Unit (SKPD) is still very low, especially at the beginning of the fiscal year, namely in Quarter I and II. Partially, Budget planning does not relatively affect the budgetting absorption, meanwhile budget implementation positively and significantly influence the budgetting absorption. However, it experienced a very significant increase in uptake at the end of the year namely in the third and fourth quarter. The influence of variables was measured using multiple linear regression analysis. The results of the study indicate that budget planning and budget execution have a significant simultaneous influence on the absorption of the SKPD budget. The budget planning coefficient is 0.068, which means that if budget planning increases by one unit of calculation, the budget absorption will increase by 0.068 times or 6,8 % assuming other variables are not altered. The budget implementation coefficient is 0,423, which means that if budget execution increase by one unit of calculation, the budget obsorrption will increase by 0,423 times or 42,3 % assuming other variables are not altered.